Association between lower body qualities and change-of-direction performance: A meta-analysis - Chen, Z.; Yin, M.; Bishop, C.; Ainsworth, B.; Li, Y. (International Journal of Sports Medicine, 2023)
The aim of the present study is to determine the associations between lower body muscle strength qualities and change of direction (CoD) performance. Three databases were used to perform a systematic literature search up to September 30, 2022. Based on the studies that met the inclusion criteria, we calculated Pearson`s r correlation coefficient to examine the relationships between muscle strength qualities and CoD performance. The quality of the studies included was evaluated by the modified version of the Downs and Black Quality Index Tool. Heterogeneity was determined via the Q statistic and I 2, and Egger`s test was used to assess small study bias. The results revealed that lower body maximal strength (pooled: r=- 0.54, dynamic: r=- 0.60, static: r=- 0.41), joint strength (pooled: r=- 0.59, EXT-ecc: r=- 0.63, FLEX-ecc: r=- 0.59), reactive strength (r=- 0.42) and power (pooled: r=- 0.45, jump height: r=- 0.41, jump distance: r=- 0.60, peak power: r=- 0.41) were negatively and moderately related to CoD performance. To conclude, the results highlight that a number of muscle strength qualities are associated with CoD performance and are pertinent to specific phases of a directional change. It should be noted that the conclusions of this study do not establish causality, and further research is needed to better understand their training effects and underlying mechanisms.